2020
DOI: 10.1109/tnsre.2020.2987357
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Four Approaches to Evaluate the Sit-to-Stand Movement

Abstract: The sit-to-stand test (STS) is a simple test of function in older people that can identify people at risk of falls. The aim of this study was to develop two novel methods of evaluating performance in the STS using a low-cost RGB camera and another an instrumented chair containing load cells in the seat of the chair to detect center of pressure movements and ground reaction forces. The two systems were compared to a Kinect and a force plate. Twenty-one younger subjects were tested when performing two 5STS movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…influence STS performance [ 10 ]. Consequently, many studies have attempted to gain insight into the STS movement through biomechanical analyses with various systems such as force plates, combined with or without optoelectronic systems [ 8 , 11 , 12 , 13 , 14 , 15 ], video analysis [ 16 ], goniometry [ 17 , 18 ], and more recently accelerometry [ 15 , 19 , 20 , 21 ]. The recent technological progress involving wearable sensors allows for a more comprehensive analysis of the biomechanical kinematic variables of STS in clinical settings [ 22 ], which could be used in place of expensive and time-consuming biomechanical laboratory evaluations [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…influence STS performance [ 10 ]. Consequently, many studies have attempted to gain insight into the STS movement through biomechanical analyses with various systems such as force plates, combined with or without optoelectronic systems [ 8 , 11 , 12 , 13 , 14 , 15 ], video analysis [ 16 ], goniometry [ 17 , 18 ], and more recently accelerometry [ 15 , 19 , 20 , 21 ]. The recent technological progress involving wearable sensors allows for a more comprehensive analysis of the biomechanical kinematic variables of STS in clinical settings [ 22 ], which could be used in place of expensive and time-consuming biomechanical laboratory evaluations [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study, 19) the results of the phase-determination rule-based algorithm interpreting the time-weight curve of a loadcell-embedded chair were generally similar, although researchers adopted a percent cut-off value to define phases rather than the absolute weight value as used in the present study. Al- though a single loadcell sensor could reliably measure STS, as demonstrated by Shukla et al 19) , we noted that rule-based algorithms based on loadcell data were sometimes less reliable in capturing STS phases, especially in frail and underweight female patients in real-world settings. To address this issue, we added a Li-DAR set at 45° to further acquire time-distance data by tracking the distance between the sensor and buttock of the participants.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have attempted to capture the dynamics of 5STS using different sensors such as accelerometers, motion capture devices, force plates, depth cameras, and RGB cameras. [18][19][20][26][27][28][29] Shukla et al 19) showed that a force plate or loadcell-embedded seat could more accurately capture 5STS than depth or RGB cameras, with a smaller mean error size compared to a human expert examiner. In the study, 19) the results of the phase-determination rule-based algorithm interpreting the time-weight curve of a loadcell-embedded chair were generally similar, although researchers adopted a percent cut-off value to define phases rather than the absolute weight value as used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations